PENGUATAN KOMPETENSI SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS RISET DI PERGURUAN TINGGI - Ramdhansyah, Ramdhansyah; Triadiarti, Yulita; Zainal, Andri; Hidayat, Taufik; Sibarani, Choms Gary GT (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2025)
This study aims to develop a comprehensive model that can be used to improve the quality of research in universities in the digital era, while also testing its feasibility. The model was developed using a qualitative approach, using in-depth interviews and focus group discussions (FGDs) with department officials and lecturers. Content validity was used to test its feasibility. This study produces a lecturer competency development model to improve research quality in the digital era, consisting of four integrated pillars: Digital Literacy, Research Methodology Enhancement, Academic Writing Competency, and Continuous Learning Adaptation. The feasibility test results indicate that this model is suitable for use as a strategy to improve lecturer competency in research and scientific publications. This research provides an original contribution in integrating lecturer competency development to improve the quality of research that is adaptive to digital transformation.